Spatial and temporal variability of Jack mackerel Trachurus murphyilarvae in Peru between 1966 –2010 - Ayón, Patricia (2013)
Constant presence of Jack mackerel Trachurus murphyilarvae in the Peruvian sea between 1966 and 2010 was confirmed by an analysis of their spatial and temporal variability. In general, there is a slight positive trend in abundance of Jack mackerelT. murphyilarvae, with noticeable changes in their spatial distribution and high interannual variability. High abundance of larvae is observed in some years, which are usually followed by a longer sequence of poor abundance years. Yearly averages varied between 3 and 79 larvae/m 2 . The spatial distribution of average larvae density showed three notorious periods along time: the first between 1970 and 1979 with higher larvae densities south of 14°S; the second between 1980 and 1999 with the higher densities to the north of 14°S; and the third between 2000 and 2010 with higher densities south of 18°S. The displacement of the centers of gravity of the spatial distribution marked three noticeable periods: between 1966 and 1978 were more coastal, south of 14°S; between 1979 and 1994 more oceanic and north of 14°S; and between 1995 and 2010 which were at an intermediate position. The relationship of larvae density with oceanographic variables as well as with the distribution of adult and juvenile Jack mackerel T. murphyiare discussed, stressing the observation that there is a main center of permanent spawning activity of this species in Peruvian waters